REASONABLE ACCOMMODATIONS FOR PERSONS WITH DISABILITIES IN ELECTRONICS JUSTICE SYSTEM (E-COURT) - Panggabean, Siska Naomi (Jurnal Hukum dan Peradilan, 2021)
The emergence of e-Court as a modernization on trials enabled the judicial process to run online. The application allowed users, including Persons with Disabilities (PwD). Since the online system is essentially similar to the on-site one, the judicial process should consider reasonable accommodation. Moreover, considering Government Regulation Number 39 of 2020 concerning Reasonable Accommodations for Person with Disabilities (Regulation of Reasonable Accommodation in Judicial Process), the types of accommodations to enable PwD to use the online system must be clear. How the reasonable accommodations provided in e-Court is the issue of this research. The method of research used to elaborate on this issue is the normative juridical method. Patterns of problem approach are statute approach and conceptual approach. Meanwhile, the Analytical Descriptive method is used to construct the data. In this writing, automated online web accessibility tests showed that the medium percentage of the e-Court's accessibility is used to bolder the analysis. This writing elaborated the accessibility of e-Court and the components of the information within which needed to be enhanced for providing reasonable accommodation for Persons with Disabilities, mainly in the form of service. It also touched on the Standard of Judicial Process involving Persons with Disabilities and the provision of the Companion and/ or the Translator for Persons with Disabilities during the trial process linked with the personal assessment and the participation of society.